Features of the Right Hepatic Lobe Transplantation from a Live Family Donor with Different Types of Venous Outflow Reconstruction - O.H. Kotenko; A. A. Minich; M. C. Grygorian (Transplantation and artificial organs, 2020)
Changes in liver blood flow and functional status of liver transplants with different types of venous outflow reconstruction have not been fully studied. A graft with optimal blood flow characteristics in a living family donation is one of the key factors that determines its functional state. The Aim. Comparison of regional hemodynamics of the liver and biochemical parametersof blood after transplantation of the right lobe from a living related donor with and without amedian vein.Materials and methods. Based on our algorithm, which included analysis of the variational anatomy of the hepatic veins of the donor to determine the type of dominant vein, transplants were selected for 76 recipients: 39 patients (group 1) were transplanted right lobe of the middle vein and 37 patients (group 2) – right lobe without meddle vein. For comparative analysis, we used data from blood biochemical parameters and data from regional hemodynamics of grafts: volumetric portal blood flow, linear velocity and resistance index in the hepatic artery in both groups during the first week and on the 10th, 14th, 21st, 30th day after transplantation.Results. Using the described graft selection algorithm, we obtained the following results on the 30th day after transplantation: in group 1 there were higher values of volumetric portal blood flow compared to group 2 at all stages of observation (1110 ± 62 ml/min and 922 ± 41 ml/min, p = 0,013864 in groups 1 and 2, respectively); the resistance index in the hepatic artery was statistically significantly higher in group 2 – 0.61 ± 0.01 compared with group 1 (0.63 ± 0.01, p = 0.042722); serum bilirubin level in group 1 was statistically significantly lower compared to group 2 (33.4 ± 9 and 39.8 ± 3.4 μmol/l, respectively, p = 0.0377); serum transaminases, alanine aminotransferase and aspartate aminotransferase, were statistically significantly lower in group 1 compared with group 2 – alanine aminotransferase – 50 ± 3.3 and 78.6 ± 8.2 U/l, respectively (p = 0.0022), aspartate aminotransferase – 42 ± 2.9 and 62.4 ± 8.9 U/l, respectively (p = 0.0282)).Conclusions. With the dominant type of middle hepatic vein in transplants of the right lobe, it is necessary to perform the right lobe of the liver with the middle vein. If the right vein is dominant – the right lobe of the liver without the inclusion of the middle vein. Adequate venous outflow, with a sufficient volume of the graft of the right lobe of the liver, determines the functional mass of the graft.